OPTIMASI MODEL HIDROLOGI MOCK DAERAH TANGKAPAN AIR WADUK SEMPOR - Hilda Julia (AGRIUM: Jurnal Ilmu Pertanian, 2014)
Hydrological analysis is an important stage in water resources development activities, where the output of the analysis will give an overview about water discharge (inflow) into reservoir which is hopefully the quantity of water can supply all human needs (outflow) and also determine the direction of water resources development strategy in a comprehensive indirectly. Utilization of Mock’s hydrological model is an approach to simulate and forecast the hydrological phenomenon that is occuring in the future using certain hydrological data recording. The main input of Mock’s hydrological model are semimonthly precipitation, evapotranspiration and parameters, while the output of model is water discharge. Microsoft excel was used in analysis of data. The optimal parameters of Mock’s hydrological model for regional water catchment area of Sempor Reservoir was obtained through the stages of calibration, verification and validation. The optimal parameters are water catchment area 44.158 km2; wet season infiltration coefficient 0.25; dry season infiltration coefficient 0.4; initial soil moisture 100 mm; soil moisture capacity 150 mm; initial groundwater storage 500 mm; groundwater recession constant 0.995. Keywords: Mock’s hydrological model, water discharge, Sempor Reservoir